2009
DOI: 10.1007/s10750-009-9900-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of macroinvertebrate community structure and driving environmental factors in natural and wastewater treatment ponds

Abstract: Eutrophication still continues to be an issue of major concern for the protection of water quality, and accordingly, the European Union Water Framework Directive has set a minimum target for all waters where ''good status'' is defined as a slight departure from the biological community which would be expected in conditions of minimal anthropogenic impact. The use of constructed ponds for wastewater treatment aimed at achieving this target has shown to be an effective alternative to conventional systems in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Miguel-Chinchilla et al (2014) have recently demonstrated that environmental factors better explain the pond biodiversity than pond age, influencing the number and type of taxa that are able to colonize man-made ponds. However, the creation of constructed wetlands has the potential to provide a habitat that may be unavailable within the surrounding landscape (Becerra-Jurado et al, 2009). Thus, a more integrated management of water quality and biodiversity enhancement, as suggested by the integrated constructed wetlands concept (Harrington and Ryder, 2002;Harrington et al, 2005;Scholz et al 2007), is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miguel-Chinchilla et al (2014) have recently demonstrated that environmental factors better explain the pond biodiversity than pond age, influencing the number and type of taxa that are able to colonize man-made ponds. However, the creation of constructed wetlands has the potential to provide a habitat that may be unavailable within the surrounding landscape (Becerra-Jurado et al, 2009). Thus, a more integrated management of water quality and biodiversity enhancement, as suggested by the integrated constructed wetlands concept (Harrington and Ryder, 2002;Harrington et al, 2005;Scholz et al 2007), is required.…”
Section: Discussionmentioning
confidence: 99%
“…Research on constructed wetlands has most frequently been addressed to evaluate their efficacy in pollution removal and flood mitigation, with less attention to their role as ecosystems (Mitsch et al, 1998;Spieles et al, 2006). Only a few studies (Spieles and Mitsch, 2000;Fairchild et al, 2000;Balcombe et al, 2005;Becerra-Jurado et al, 2009;Gallardo et al, 2012) have analysed the macroinvertebrate communities of constructed wetlands and the environmental factors that influence them. A deeper knowledge of the biodiversity hosted in these environments is needed to determine if artificially created ponds and constructed wetlands are also appropriate restoration tools for biological conservation (Ruhí et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these older pond types more recent constructed wetlands have also proved valuable for wildlife, e.g. motorway stormwater retention ponds (Scher and Theiry, 2005) and farm wastewater treatment systems (Becerra-Jurado et al, 2009). Our changing patterns of land use continue to create new pond types.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrate that at a landscape-scale, different environmental factors influenced invertebrate communities in meadow (physicochemical and spatial) and urban (biological and physicochemical) environments (Table 7.10) and will be discussed in greater detail below. The results from this study (Figure 7.1,7.4,7.7) demonstrate that the greatest macroinvertebrate diversities within ponds at regional and landscape scales were associated with greater connectivity, proximity to other waterbodies, increased pond area and aquatic macrophyte cover, whilst the lowest diversities were associated with the drying of the pond basin) Biggs et al, 2005;Della Bella et al, 2005;Williams et al, 2008;Becerra-Jurado et al, 2009;Bazzanti et al, 2010). SP+B|P (%) 1.9 n/a n/a 0.4 P+B+SP (%) 0 n/a n/a 1.8…”
Section: Spatial Patterns In Macroinvertebrate Assemblage Dissimilaritymentioning
confidence: 63%